Genetic variability among seedling origin tree population of mango (Mangifera spp.) in Himachal Pradesh, India - Bhoyar, Mahesh G; Kumar, Krishan (Bangladesh Journal of Botany, 2020)
A survey to the existing seedling origin tree population of wild Mangifera spp. was carried out at Hamirpur and Kangra districts of Himachal Pradesh, India. Eighty one healthy and bearing tree population originated from seedlings in the region were marked. Wide range of genetic variability in qualitative and quantitative characters were observed for fruit, stone, peel, pulp and other fruit characters. Hamirpur district exhibited a variety in quality of fruits with varied fruit shape, colour, attractiveness etc. The significant variation was observed for different fruit parameters like fruit dimensions, fruit weight, fruit volume, stone weight, stone length, of stone, stone thickness, of stone, pulp weight, peel weight, per cent of edible and nonedible portions, ratio of stone weight to pulp weight, ratio of peel weight to pulp weight, skin thickness and TSS (Total Soluble Solids). The selected genotypes could be classified into different categories based upon their utility, viz., pickle, sucking, table purposes etc.